The Influence Of Website Quality, Security, And Trust On Purchase Decisions In The Shopee Application - Syafira Delviana; Rahmiati Rahmiati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine the effect of website quality, security and trust on purchasing decisions on the Shopee application. The method in this study uses quantitative methods. This research was conducted in the area of Padang Ngeri University. For this experiment, a probability sampling approach was used to choose the sample. Up to 200 Padang State University students who use Shopee will take part in the survey as responders. This study demonstrates that customers' trust in Shopee-compatible online marketplaces directly and favorably affects their willingness to shop there, Website quality has a positive and significant effect on consumer trust through online purchase decisions on online buying and selling sites on the application Shopee, Security online purchases has a positive and significant effect on online purchase decisions mediated by customer trust on online buying and selling sites on the Shopee application, Security online purchases has a positive and significant effect on customer trust through online purchase decisions on online buying and selling sites on the Shopee application , customer trust has a positive and significant effect on online purchase decisions on online buying and selling sites on the Shopee application.